Learning Process of Parents with Children of Attention Deficit and Hyperactivity Disorder (ADHD) in Reception - Ufairo, Auliya Adilah; Supriyono, Supriyono; Sucipto, Sucipto (Universitas Negeri Padang, 2023)
Ideally, every parent wants a child who is physically and psychologically healthy. However, the reality on the ground shows that there are children who are born or grow up in abnormal conditions and require special attention. Attention deficit hyperactivity disorder (ADHD) is a developmental disorder that is related to a person's neurology. Out of school education is a realm of education that intersects with several elements, one of which is parents. Thus, this research refers to the learning process of parents with children with attention deficit hyperactivity disorder (GPPH) in self-acceptance and learning. The research that will be carried out uses qualitative research methods with a case study approach and aims to describe the social problems faced, the learning process in acceptance, and learning resources for parents in the @temanadhd parent community. Based on the research that has been conducted, it can be seen that parents experience social problems related to their children's conditions. Parents overcome this problem by joining and learning in the @temanadhd community which acts as a forum for facilitating parents' learning. The learning processes and resources used by parents are information from various sources, training and seminars on parenting and self-acceptance.